Increasing Student Engagement through Mobile Learning in Mathematics Subjects - Sri Tirto Madawistama; Yuanyuan Wang; Amelia Hayati; Rachmasari Pramita Wardhani; Mohammad Edy Nurtamam (Yayasan Adra Karima Hubbi, 2024)
Background. Learning in this century has experienced a significant transformation, especially with the emergence of mobile learning technology. In this context, learning Mathematics becomes an important focus because it is often considered a challenging subject for some students. The problem that arises is the lack of student involvement and difficulty in understanding Mathematics concepts. Purpose. This research aims to explore the effectiveness of mobile learning in increasing student involvement in Mathematics learning. By using a quantitative approach through a survey model, this research aims to collect data from mathematics education teachers and students to understand the impact of mobile learning in a broader learning context. Method. This research will adopt a quantitative approach using a survey model. Researchers will compile a questionnaire in the form of a questionnaire with carefully prepared answer choices, and then collect it via the Google Form platform. The research subjects consisted of 30 respondents who were mathematics education teachers and students, who were chosen randomly from the existing population. Results. The results of the questionnaire analysis showed that the use of mobile applications in mathematics learning had a positive impact on student engagement, learning motivation, and sense of trust. themselves in solving mathematical problems. However, there is still room to improve interaction between students and teachers through mobile applications. Conclusion. Overall, this research shows that mobile learning has great potential in improving Mathematics learning by increasing student engagement and strengthening interactions between students and teachers. However, further adjustments and developments need to be made to mobile applications to maximize their potential in a broader learning context.